2023
DOI: 10.3390/cells12121663
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Alpha-1-Antitrypsin Deficiency in Patients with Biliary Tract Cancer and Its Associated Clinicopathological Features

Abstract: Alpha-1 antitrypsin deficiency (A1ATD) is underdiagnosed and associated with liver diseases. Here, we genotyped 130 patients with biliary tract cancer (BTC) scheduled for liver resection and found A1ATD in 10.8% of the patients. A1ATD was found in all BTC subtypes, and patients had similar clinical features as non-A1ATD BTC, not permitting their identification using clinical routine liver tests. In intrahepatic cholangiocarcinoma (iCCA), the abundance of A1AT protein was increased in the tumor and appeared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This should be considered an added value in the design of new cosmeceutical ingredients, whose claims are rarely supported by appropriate studies but rather anecdotally reported. In addition to the cosmeceutical application, evidence on the implication of neutrophil serine proteases (NSPs) such as elastase, proteinase 3 (PR3), cathepsin G (CatG), and matrix metalloproteases (MMPs) as pathogenic determinants of chronic inflammatory lung disorders that are associated with increased protease activity suggest potential interest of a further investigation of the use of short sequences derived from serpin A1 for pharmaceutical applications. , Moreover, another possible application to be investigated is the use of this peptide to compensate for α-1-antitrypsin deficiency (A1TD), which is an under-diagnosed pathology associated with chronic obstructive pulmonary disease (COPD) and chronic liver diseases. …”
Section: Discussionmentioning
confidence: 99%
“…This should be considered an added value in the design of new cosmeceutical ingredients, whose claims are rarely supported by appropriate studies but rather anecdotally reported. In addition to the cosmeceutical application, evidence on the implication of neutrophil serine proteases (NSPs) such as elastase, proteinase 3 (PR3), cathepsin G (CatG), and matrix metalloproteases (MMPs) as pathogenic determinants of chronic inflammatory lung disorders that are associated with increased protease activity suggest potential interest of a further investigation of the use of short sequences derived from serpin A1 for pharmaceutical applications. , Moreover, another possible application to be investigated is the use of this peptide to compensate for α-1-antitrypsin deficiency (A1TD), which is an under-diagnosed pathology associated with chronic obstructive pulmonary disease (COPD) and chronic liver diseases. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PNI may serve as a substitute for biological markers of invasive disorders that reflect tumor or stage-specific characteristics substantially. In PNI-positive ICC patients, molecules associated with a poorer prognosis for ICC, such as NPY1R , A1ATD , GPX4 , and KRAS mutations, exhibit elevated levels ( 33 - 36 ). Future research should focus on elucidating the molecular mechanism behind tumor-nerve interactions and PNI-related carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%